Circular RNA profiles and the potential involvement of down‐expression of hsa_circ_0001360 in cutaneous squamous cell carcinogenesis. Issue 4 (11th March 2021) - Chen, Pingjiao; Li, Changxing; Huang, Hongchang; Liang, Liuping; Zhang, Jing; Li, Qian; Wang, Qi; Zhang, Sanquan; Zeng, Kang; Zhang, Xibao; Liang, Jingyao
Abstract : Circular RNAs (circRNAs) act as sponges of noncoding RNAs and have been implicated in many pathophysiological processes, including tumor development and progression. However, their roles in cutaneous squamous cell carcinoma (cSCC) are not yet well understood. This study aimed to identify differentially expressed circRNAs and their potential functions in cutaneous squamous cell carcinogenesis. The expression profiles of circRNAs in three paired cSCC and adjacent nontumorous tissues were detected with RNA sequencing and bioinformatics analysis. The candidate circRNAs were validated by PCR, Sanger sequencing and quantitative RT‐PCR in another five matched samples. The biological functions of circRNAs in SCL‐1 cells were assessed using circRNA silencing and overexpression, 3‐(4, 5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2H‐tetrazolium inner salt (MTS), flow cytometry, transwell and colony formation assays. In addition, the circRNA–miRNA–mRNA interaction networks were predicted by bioinformatics. In summary, 1115 circRNAs, including 457 up‐regulated and 658 down‐regulated circRNAs (fold change ≥ 2 and P  < 0.05), were differentially expressed in cSCC compared with adjacent nontumorous tissues. Of four selected circRNAs, two circRNAs (hsa_circ_0000932 and hsa_circ_0001360) were confirmed to be significantly decreased in cSCC using PCR, Sanger sequencing and quantitative RT‐PCR. Furthermore, hsa_circ_0001360 silencing was found to result in a significant increase of the proliferation, migration and invasion but a significant decrease of apoptosis in SCL‐1 cells in vitro, whereas hsa_circ_0001360 overexpression showed the opposite regulatory effects. hsa_circ_0001360 was predicted to interact with five miRNAs and their corresponding genes. In conclusion, circRNA dysregulation may play a critical role in carcinogenesis of cSCC, and hsa_circ_0001360 may have potential as a biomarker for cSCC. Abstract : The expression profiles of circular RNAs (circRNAs) were analyzed using high‐throughput RNA sequencing between paired cutaneous squamous cell carcinoma and adjacent nontumorous tissues. In total, 1115 circRNAs (457 up‐ and 658 down‐regulated circRNAs) were differentially expressed in cutaneous squamous cell carcinoma. Down‐regulation of hsa_circ_0001360 significantly increased proliferation, migration and invasion but decreased apoptosis of SCL‐1 cells in vitro, whereas up‐regulation of hsa_circ_0001360 had the opposite effects.